Practicing physical exercise and symptoms of depression in college students - Rondina, Regina de Cassia; Aragão Martins, Raul; Pereira da Silva, Ana Luiza; Pini Alves Mascarenhas, Gabriel; Garcia Travenssolo, Joice; dos Santos, Bruno Luiz (O Mundo da Saúde, 2018)
This study investigated the relationship between the symptoms of depression and physical activity patterns in university students seen by the Psychological Assistance Center at a Public University, between 2014 and 2015. In order to collect information on sociodemographic characteristics, physical activity patterns and performance of students in the Beck Depression Inventory (BDI-II), a survey of information was taken from the registration forms of the clientele who sought for assistance. Among the respondents, 38.9% had scores in the severe range of the BDI-II. Regular physical exercise was reported by 36.2% of students, 30.8% reported not practicing physical exercise and 33.1% reported having abandoned the practice. There was no significant difference between the mean scores of the three groups in the BDI-II. The difference between the means of practitioners and former practitioners is marginal (p = 0.084). This may be due to the interaction between different variables. Further studies are needed to confirm these results. Knowledge on this issue is necessary, in order to improve preventive and therapeutic actions in mental health, with characteristics specifically designed for this clientele. Strategies such as providing information and awareness of students about the relationship between mental health and lifestyle aspects such as physical inactivity/ physical activity, regular sleep, and diet (among others) could be used for this purpose.